2018
DOI: 10.1590/1413-70542018425020718
|View full text |Cite
|
Sign up to set email alerts
|

The different response of sugarcane genotypes in multiple stress

Abstract: Research focused on identify abiotic stress-tolerant genotypes is highly desirable since their use may reduce costs of soil and crop management and productivity losses. The aim of this study was to determine the behavior of 24 sugarcane genotypes under high levels of Al 3+ and Mn 2+ associated with low availability of mineral nutrients. The experiment was carried out under greenhouse condition in a 24 × 2 factorial scheme (24 genotypes × 2 treatments: with and without stress), and four replications in complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…The fact that aluminum content increased only in the root confirms the observations that this element has preferential accumulation in the root system, with a small amount translocated to the shoot, thus showing its low mobility in the plant (Yan et al, 2018;Li et al, 2018). Thus, symptoms of Al toxicity in the aerial part are not always easily identifiable (Souza et al, 2016;Sousa;Cazetta;Nascimento, 2018) and, unlike the root system, it has little direct effect on that part of the plant, mainly in a relatively short period of time (Rossiello;Jacob-Netto, 2006). The high availability of Al in the growing environment can also induce nutrient deficiency due to its interference in the solubilization/precipitation processes in the solution, uptake by roots, transport, and use of nutrients in the plant.…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…The fact that aluminum content increased only in the root confirms the observations that this element has preferential accumulation in the root system, with a small amount translocated to the shoot, thus showing its low mobility in the plant (Yan et al, 2018;Li et al, 2018). Thus, symptoms of Al toxicity in the aerial part are not always easily identifiable (Souza et al, 2016;Sousa;Cazetta;Nascimento, 2018) and, unlike the root system, it has little direct effect on that part of the plant, mainly in a relatively short period of time (Rossiello;Jacob-Netto, 2006). The high availability of Al in the growing environment can also induce nutrient deficiency due to its interference in the solubilization/precipitation processes in the solution, uptake by roots, transport, and use of nutrients in the plant.…”
Section: Resultssupporting
confidence: 63%
“…The reduction in the root and shoot dry matter found in this study was also observed by Sousa, Cazetta and Nascimento, (2018) in 24 sugarcane genotypes, Barbosa et al (2017) with wheat and Riaz et al (2018) with trifoliate orange. Therefore, the increased aluminum contents lead to a decrease in root and shoot dry matter production (Wang et al, 2016;Sousa;Cazetta;Nascimento, 2018). Root ends are the most affected, and their response to Al occurs very quickly, which indicates that at first, Al inhibits root cell expansion and elongation, and then cell division is inhibited (Ecco;Santiago;Lima, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations